Examining The Relationship between Electricity Consumption, Financial Development and Economic Growth in ASEAN Countries: Evidence from a Bayesian Analysis - Hoang, Canh Chi (International Journal of Energy Economics and Policy, 2021)
The literature has suggested that financial development and electricity consumption are key determinants of economic growth. However, existing studies usually was applied the frequentist inference, which is an outdated estimator. By applying the Bayesian approach via the Metropolis-Hasting and Gibbs samplers as the MCMC methods, the study aims to re-examine the impact of financial development and electricity consumption on economic growth in ASEAN+6 countries from 1980 to 2016. The obtained outcome shows that the impact of both financial development and electricity consumption is strong and positive on economic growth. There is a uni-directional causality running from economic growth to energy consumption, supported the Conversation hypothesis. Based on the empirical result, several policy implications are suggested for emerging countries, ASEAN+6 nations, in particular. Keywords: Financial development; Energy consumption; Economic growth; Bayesian; ASEAN countries. JEL Classifications: F43, O13, O47, Q42, Q43. DOI: https://doi.org/10.32479/ijeep.10642